THE PERFORMANCE OF PUBLIC TRANSPORTATION RELATED TO THE PUBLIC SERVICE PROVISION - Meita Triana Indah Puri, Mrs. (FIA UB, 2012)
One important element of developed and developing countries is the transportation because there are activities of the population with a range of social and economic mobility which needed transportation to cover their mobility. It afflicts to all large cities in both developing and developed countries that produces broadly similar results such as traffic congestion, parking difficulties, accidents, crowded public transport, environmental damage, and bad conditions for pedestrian. In this research, the researcher concerns in the condition of public transportation. In most cities, public transportations have roles in alleviating traffic congestion, parking difficulties and the environmental impacts of commuting by automobile. In fact, public transportation is not able to compete with private vehicle. Public transportation should be able to give security and safety guarantee to the passengers.The purpose of this research is comparing the performance of public transportation in both South Tangerang City, Indonesia and Hat Yai City, Thailand. In this research, there are three research methods; document analysis, observation, and interview. The interviewees include government sector, private sector, and civil society. In conclusion, the dominant problems of public transportation performance which are faced in both South Tangerang City, Indonesia and Hat Yai City, Thailand are related to the lack of supporting facilities, the inappropriate habits of the driver, the criminal action inside public transportation, the existence of illegal driver, influenced by the political factor, have an old physical condition, and lack of assertive sanction for the drivers who violate the traffic regulations.